North Natuna Waters Dispute Resolution - Johan, Suwinto; Kurnia, Ida (Kertha Patrika; Vol 45 No 1 (2023), 2023)
This study seeks to discuss the most effective ways to resolve conflicts in the North Natuna Sea. China has repeatedly violated the North Natuna waters. The Indonesian government has carried out security in the North Natuna waters. This dispute resolution has not found the best way for Indonesia or China. Indonesia claims North Natuna waters governed by the Law of the Sea Convention of the United Nations (UNCLOS 1982) while China claims North Natuna waters unilaterally based on the nine-dash line. The Natuna dispute has become a national issue in Indonesia. A normative legal methodology is employed in this study. The research discussion does not only focus on disputes but also on the relationship with the environment. This study concludes that the sea is a very important source of biological life. Every country has an interest in marine waters. Biological resources in the sea are always moving and sometimes their rights and authority are transferred to other countries. Biological marine resources have an ecosystem of living life. The Indonesian government must take a prudent stance on the dispute over the North Natuna waters with the Chinese government. North Natuna waters have strategic value for many countries, not only Indonesia.